Effect of sodium-glucose cotransporter protein-2 inhibitors on left ventricular hypertrophy in patients with type 2 diabetes: A systematic review and meta-analysis - Wang, Yao; Zhong, Yujie; Zhang, Zhehao; Yang, Shuhao; Zhang, Qianying; Chu, Bingyang; Hu, Xulin (Frontiers in Endocrinology, 2023)
Abstract Objective: This systematic review and meta-analysis was performed to compare the effect of sodium-glucose cotransporter protein-2 inhibitors (SGLT-2i) and placebo on left ventricular hypertrophy (LVH) in patients with type 2 diabetes. Method: Randomized controlled trials (RCTs) comparing the LVH parameters of SGLT-2i to placebo in patients with type 2 diabetes were included. Our primary outcomes were the changes in left ventricular mass (LVM) and left ventricular mass index (LVMI) from baseline to the study endpoint. Secondary outcomes were the changes in left ventricular end-diastolic volume (LVEDV), left ventricular end-systolic volume (LVESV), left ventricular ejection fraction (LVEF), and the ratio of early mitral inflow velocity to atrial inflow velocity (E/A). Summary odds ratios were estimated using a fixed-effect or random-effect model. Results: A total of 11 articles were included. Data were extracted from 11 original studies matching our inclusion criteria. In our meta-analysis, there were significant improvement in LVM (SMD -0.23, 95% CI -0.44 to -0.02, I2 = 22.6%, P = 0.034), LVMI (SMD -0.25, 95% CI -0.38 to -0.12, I2 = 0.0%, P = 0.000), LVEDV (SMD-0.19, 95% CI -0.36 to-0.01, I2 = 62.3%, P = 0.035) and LVESV (SMD -0.21,95% CI -0.39 to -0.04, I2 = 32.9%, P = 0.017) in the SGLT-2i group compared with the placebo group. Furthermore, no significant differences were found in LVEF (SMD 0.13, 95% CI 0.00 to 0.26, I2 = 0.0%, P = 0.050) and E/A (SMD-0.01, 95% CI -0.22 to 0.20, I2 = 0%, P = 0.908) between the two groups. Conclusions: This meta-analysis confirmed the beneficial effects of SGLT-2i on reversal of left ventricular remodeling. The LVH regression was more pronounced in studies of type 2 diabetes patients receiving SGLT-2i than placebo.